Effect of sonoprocessing on the quality of plant-based analog foods: Compatibility to sustainable development goals, drawbacks and limitations - Gultekin Subasi, Busra Id Orcid -. -. -.; Bilgin, Aysenur Betul; Günal-Köroğlu, Deniz; Saricaoglu, Beyza; Haque, Shafiul; Esatbeyoglu, Tuba; Capanoglu, Esra (Elsevier BV, 2024)
Sonoprocessing (US), as one of the most well-known and widely used green processing techniques, has tremendous benefits to be used in the food industry. The urgent call for global sustainable food production encourages the usage of such techniques more often and effectively. Using ultrasound as a hurdle technology synergistically with other green methods is crucial to improving the efficiency of the protein shift as well as the number of plant-based analog foods (PBAFs) against conventional products. It was revealed that the US has a significant impact when used as an assistant tool with other green technologies rather than being used alone. It increases the protein extraction efficiencies from plant biomasses, improves the techno-functional properties of food compounds, and makes them more applicable for industrial-scale alternative food production in the circular economy. The US aligns well with the objectives outlined in the UN's Sustainable Development Goals (SDGs), and Planetary Boundaries (PBs) framework, demonstrating promising outcomes in life cycle assessment. However, several challenges such as uncontrolled complex matrix effect, free radical formation, uncontrolled microbial growth/germination or off-flavor formation, removal of aromatic compounds, and Maillard reaction, are revealed in an increased number of studies, all of which need to be considered. In addition to a variety of advantages, this review also discusses the drawbacks and limitations of US focusing on PBAF production.
Keywords: Plant-based; Food Handling; Acoustics. Sound; QC221-246; Green Chemistry Technology; Sonoprocessing; Sustainable Development; Plants; Plant protein; Chemistry; Food Quality; Sustainable US Technology; Analog foods; QD1-999; Goals; Ultrasound modification